ANALISIS POTENSI DAN PENGEMBANGAN AGRIBISNIS SAYURAN DI KABUPATEN KARANGANYAR - Ratih Dwi Kartikasari; suswadi; sutarno (JURNAL ILMIAH AGRINECA, 2021)
Karanganyar Regency has a strategic role in economic development in Indonesia, especially in the agricultural sector. This study aims to determine the potential for agribusiness development, especially vegetable commodities in Karanganyar Regency by using the Location Quotient (LQ) method. Mapping with the LQ method will produce commodities that are classified as basic or non-basic commodities that can contribute to the welfare of farmers, especially increasing income. The data used are secondary data about vegetable production in Karanganyar Regency in 2019 and primary data from interviews with farmers. The results showed that there were 6 vegetable commodities cultivated in 17 districts, namely onions, large chilies, potatoes, cabbage, Chinese cabbage, tomatoes, and garlic. The highest LQ value is large chili, while the second to lowest is onions, potatoes, tomatoes, and Chinese cabbage. The white yawl commodity has not become a base commodity because the LQ value is <1 in all districts in Karanganyar Regency.